2011
DOI: 10.1111/j.2042-3292.2011.00296.x
|View full text |Cite
|
Sign up to set email alerts
|

Undesired behaviour in horses: A review of their development, prevention, management and association with welfare

Abstract: Summary Undesired behaviours are a common problem amongst leisure and sporting horses in the UK and have a significant impact on the work of equine practitioners. In most cases, behaviours considered aberrant by owners are normal responses for their horses. Behaviours perceived as ‘naughtiness’ may in fact signify direct actions to avoid pain‐ or fear‐inducing stimuli. Examples that practitioners might deal with include trailer loading problems, avoidance of having saddlery equipment applied or reluctance to l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
40
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 60 publications
(42 citation statements)
references
References 50 publications
2
40
0
Order By: Relevance
“…One factor that could have had an effect over our results is the small amount of time that these horses spent inside their boxes, compared with the case of thoroughbreds that spend most of the day inside the box. McGreevy et al (1995ª) found that the risk of presentation of stereotypic behaviour increased significantly when spending less than 4 hours outside the stall, and that endurance horses spend significantly more time out of their stalls than dressage and eventing horses For animals stabled permanently or with restricted turnout, the environment limits their behavioural options considerably (Hothersall and Casey 2012) increasing the risk of developing abnormal behaviours.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…One factor that could have had an effect over our results is the small amount of time that these horses spent inside their boxes, compared with the case of thoroughbreds that spend most of the day inside the box. McGreevy et al (1995ª) found that the risk of presentation of stereotypic behaviour increased significantly when spending less than 4 hours outside the stall, and that endurance horses spend significantly more time out of their stalls than dressage and eventing horses For animals stabled permanently or with restricted turnout, the environment limits their behavioural options considerably (Hothersall and Casey 2012) increasing the risk of developing abnormal behaviours.…”
Section: Resultsmentioning
confidence: 99%
“…The development of these behaviours is generally associated with horses being managed in suboptimal environments either currently or in the past (Hothersall and Casey 2012). Some husbandry practices that have been considered as risk factors for the development of these behaviours include confinement, isolation from other horses, feeding practices, bedding material, and weaning method, among others (Broom and Kennedy 1993a , Nicol 1999, Waters et al 2002, Christie et al 2006, Clegg et al 2008, Visser et al 2008, Wickens and Heleski 2010.…”
Section: Introductionmentioning
confidence: 99%
“…Because owners often misunderstand the reason for the development of such behaviors in their horses, attempts at correcting them often involve suppression-or punishment-based approaches (Hothersall and Casey, 2012). Although repeated subjugation of undesirable fear responses may ultimately appear to solve the overt behavioral reaction, this method can cause short-or long-term stress (McGreevy and McLean, 2010) and can worsen the problem or lead to the development of alternative avoidance strategies such as abnormal behaviors (Hothersall and Casey, 2012). Besides possible problems caused by inappropriate human reactions to fear displays, a long-term negative emotional state related to fear can per se cause chronic stress and reduced welfare (Dantzer and Mormede, 1983;Désiré et al, 2006;Minch et al, 2008;Willner et al, 1992).…”
Section: Introductionmentioning
confidence: 99%
“…Keeling (1999) demonstrated that in equitation sports many serious human injuries occur as a result of unexpected horse fear reactions. Because owners often misunderstand the reason for the development of such behaviors in their horses, attempts at correcting them often involve suppression-or punishment-based approaches (Hothersall and Casey, 2012). Although repeated subjugation of undesirable fear responses may ultimately appear to solve the overt behavioral reaction, this method can cause short-or long-term stress (McGreevy and McLean, 2010) and can worsen the problem or lead to the development of alternative avoidance strategies such as abnormal behaviors (Hothersall and Casey, 2012).…”
mentioning
confidence: 99%
“…many dogs are scared by hot air balloons especially when the burner is used to help them gain height) or the intensity of emotional arousal [15] (e. g. it is normal and acceptable for a dog to be scared to some extent of a loud noise, but if this response is so intense that it results in destructive attempts to escape and self-harm when there are fireworks outside, this becomes a problem). Evaluating and managing such problems has a growing scientific basis and falls within the rapidly developing discipline of what is often referred to as clinical animal behavior [15,16] or veterinary behavioral medicine [11 ,17]; there are currently three main paradigms underpinning this field's scientific foundation [11 ]: referred to here as the Behavioral, Medical and Psychobiological Approaches. While trying to achieve a common goal in practice, they are based on different philosophical conceptualisations to the study of the emotional basis to animal behavior which has implications for the type of assessment made of emotion and the evidence used in this process.…”
Section: Introductionmentioning
confidence: 99%